Association between Weight Status and Mental Health among Korean Adolescents: A Nationwide Cross-Sectional Study - Youngha Choi; Jeana Hong (MDPI AG, 2023)
This study explored the relationship between adolescents' weight status and mental health problems. It specifically investigated the weight perceptions of obese adolescents and the effect on their mental health. This cross-sectional study was based on the data of adolescents aged 12-18 years from the Korean National Health and Nutritional Examination Survey (2010-2019). Data regarding anthropometric measurements, health conditions, and socioeconomic status were extracted, and the associations between weight status (actual, perceived, or misperceived) and mental health conditions (depressed mood, perceived stress, and suicidal ideation) were analyzed using complex sample multiple logistic regression after adjusting for possible confounders. A total of 5683 adolescents (53.1% boys and 46.9% girls) were included in this study, with a mean age of 15.1 years. Among the participants, actual, perceived, and misperceived status of being overweight were observed in 20.8%, 32.7%, and 18.4%, respectively. Additionally, depressed mood, perceived stress, and suicidal ideation were observed in 9.1%, 25.7%, and 7.4% of Korean adolescents, respectively, with higher prevalences in girls for all three conditions. Actual weight status was not significantly associated with mental health conditions in either sex. Furthermore, girls who perceived themselves to be overweight, regardless of their actual body weight, or who had overestimated their actual weight were more likely to have experienced depressed mood and stress, while boys who perceived themselves to be underweight were more likely to have experienced suicidal ideation than participants with an average weight perception or an accurate recognition of their weight status. Conversely, in overweight/obese participants, perceived weight status was not associated with mental health conditions. In conclusion, perceived weight status and its discrepancy with actual body weight were more strongly associated with an increased risk of mental health problems than actual weight status itself among Korean adolescents. Therefore, adolescents' perceptions of their body image and weight-related attitude should be assessed to promote their mental health.